IMPLEMENTATION OF THE RESTORATIVE JUSTICE CONCEPT BASED ON POLICE REGULATION NO. 8 OF 2021 IN CRIMINAL OFFENSES - Huroiroh, Ernawati; Sushanty, Vera Rimbawani; Dermawan, Alif Fito; Sitorus, Betris Kristin Ambar Wati (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
This study discusses the implementation of the Restorative Justice (RJ) concept based on Police Regulation No. 8 of 2021 concerning the Handling of Criminal Offenses in the East Java Regional Police. The background of this research stems from the emergence of the restorative justice paradigm as a response to the weaknesses of the system, which tends to neglect the rights of victims. Restorative justice offers a more humane and solution-oriented approach to criminal case resolution, emphasizing the restoration of harm and the relationship between the offender, the victim, and society. This research employs a normative method with a legislative and case study approach to analyze the juridical legitimacy and the implementation of the policy in practice. The results show that the implementation of restorative justice during the investigation process, particularly in the jurisdiction of the East Java Regional Police, has provided an alternative resolution that is faster, more efficient, and satisfying for all parties, especially in minor cases. Furthermore, restorative justice is considered to reduce the burden on the formal criminal justice system and foster substantive justice. However, challenges in implementation remain, particularly in terms of the readiness of law enforcement officers and public understanding of this new paradigm. This study recommends the strengthening of regulations, continuous training for officers, and the enhancement of public awareness to ensure the optimal application of restorative justice in accordance with the values of justice, utility, and legal certainty.